Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan DHL Jakarta - Lucianus Sutadji (STIE Widya Manggala, 2012)
The influence of service quality and price to customer satisfaction rates in DHL Headquarters, Jakarta. Since the advances in science led to the Industrial revolution in the field of communication and transportation technologies, the relations between communities in different parts of the world become more easily, more quickly and more accurately. The relationship is not only in the form of social relations and culturals, but also a relationship and exchange of goods and services commercially which causes the flow of goods and services between countries in different parts of the world. This condition is observed by a company of global courier service level because of the power of capital, human resources, communication technology, transportation technology, management systems and networks. One is where the DHL operates in partnership with their Indonesian business partner, PT. Birotika Semesta. In giving the services to the customers, DHL priority service quality based on the concept of Customer Relation Management (CRM), which basically creates consumer loyalty. However, since the area of their operations is in Indonesia, Price factors to be considered by the management of DHL, because it’s related with the purchase ability of Indonesian customer. From this research, it proved that the relationship between service quality and price to customer satisfaction was positive, significant and very strong.